Marketing Management Analysis of Customer Relationship Marketing - Syamsuddin, Fatimah (Journal Development Manecos, 2023)
This article discusses customer relationship marketing, which is a marketing strategy currently carried out by many companies who want their customers or consumers to continue to buy their products or use their services. The purpose of this writing is to determine the meaning of Customer relationship marketing (CRM), to determine the objectives of Customer relationship marketing (CRM), to determine the benefits of Customer relationship marketing (CRM), to determine supporting technology Customer relationship marketing (CRM), to determine the Customer relationship approach marketing (CRM).